Gyroscopic analysis in two-wheeler vehicles: an application oriented case study to ensure rider safety. (29th December 2008) - Rajiv, P.; Logesh, R.; Vinodh, S.
In the present competitive scenario, the number of road accidents keeps increasing. In this context, the safety of vehicle rider gains importance. Various researchers have reported the safety systems to be adopted for ensuring the rider safety. In this connection, the gyroscopic effect has a significant relationship with vehicle safety. The case study being reported in this paper narrates the gyroscopic analysis carried out for two types of two wheeler vehicles, namely, TVS XL Super and Yamaha RX 100. The investigation has been carried out for three different road conditions. Various parameters like gyroscopic couple, angular velocity of precession and balancing couple are calculated for three different road conditions. Followed by this, the graphical analysis has been carried out to determine the values of safety velocity for the two vehicles. In addition, software named 'Gyrocalci' has been exclusively designed and developed.